Tren Budaya Kontemporer: Interaksi Antara Islam dan Fenomena K-Pop di Kalangan Remaja SMAN 5 Kota Tangerang Selatan - Haniyah Qothrunnada; Nurjanah Nurjanah (Tarbiatuna: Journal of Islamic Education Studies, 2024)
In the context of cultural globalization, the views of Muslims in Indonesia on the influx of foreign cultures, especially K-Pop from South Korea, is an interesting topic to discuss. With respect to K-Pop, the interaction between Islam and the K-Pop phenomenon has become a modern cultural trend that is interesting to study in an era of increasingly connected cultural globalization, while still considering the existence and importance of existing local cultures. Both phenomena have a significant influence on the identity, lifestyle and worldview of today's youth. It is through this study that we can investigate how adolescents at SMAN 5 South Tangerang City who are Muslims respond to and interact with the K-Pop phenomenon, including how K-Pop culture affects their perceptions of social relationships, self-identity, and religious values. The focus of this study is to discuss how the phenomenon of the interaction dynamics between Islam and K-Pop culture among teenagers at SMAN 5 South Tangerang City, including the factors that influence their preference for K-Pop content, how they act on content that contradicts religious values, and how the Islamic community at the school handles the challenges and opportunities that arise from this interaction. The purpose of this study is to provide better information on how Muslim teenagers in schools cope with the challenges and opportunities that arise from these interactions. The rise of this culture, known as the “Korean Wave”, has been growing from the early 2000s to the present. Most people view K-Pop as a cultural threat that will weaken the local values found in Indonesia and undermine the quality of the existing culture. In the end, K-Pop spread because its fans came from all walks of life. It is also spreading not only because of the pop culture factor, but because of the movies, fashion, lifestyle, and culinary that are increasingly favored by Indonesians, especially Muslim teenagers. As a result, ordinary people are noticing the increasing threat of foreign K-Pop culture entering Indonesia.